Integrating Life Skills in Physical Activity Programs for Elementary School Students (Universitas Pendidikan Indonesia, 2024)
The purpose of this study was to determine the best program to improve elementary school student life skills through physical activity programs in physical education subject. In this study, sixty elementary school students in Gorontalo participating in basketball extracurricular were divided into two groups. Thirty students were included in the experimental group and other thirty students were put into the control group. The sampling technique used was the cluster random sampling technique. The Life Skills Scale for Sport (LSSS), consisting of eight elements of social skills namely leadership, problem solving, decision making, emotional skills, communication, teamwork, and goal setting, was used in this quasi-experimental study. The findings showed that elementary school student life skills improved better after receiving the physical activity program combined with life skills than the physical activity program without integrating life skills.